1995
DOI: 10.1111/j.1365-2621.1995.tb06281.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Tocopherol, β‐Carotene and Ascorbic Acid as Antioxidants in Stored Poultry Muscle

Abstract: Broilers were fed a-tocopherol or p-carotene for 3 wk or L-ascorbic acid for 24 hr prior to slaughter. u-Tocopherol maintained the redness of unheated meat stored for 8 wk (-20°C). Values for thiobarbituric acid reactive substances in ground, stored meat showed that L-ascorbic acid produced results similar to the control while a-tocopherol produced results lower than the control. Panelists rated meat with added u-tocopherol as different from the control for smell and flavor. P-Carotene was a pro-oxidant compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
2
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 16 publications
5
32
2
2
Order By: Relevance
“…The efficiency of various antioxidants inhibiting lipid oxidation throughout freeze storage was in the following order: ascorbic acid > tocopherol > BHA > control (P < 0.01). This data did not confirm the results of King et al (1995) and Serdaroglu and YildizTurp (2004), who found ascorbic acid inactive in preventing lipid oxidation on poultry at the end of the storage at -20°C for 6 weeks. When used in meat products at 0.025-0.05%, ascorbic acid and sodium ascorbate inhibited lipid oxidation and preserved the desirable meat flavour (Rhee et al 1997).…”
Section: Lipid Oxidationcontrasting
confidence: 56%
“…The efficiency of various antioxidants inhibiting lipid oxidation throughout freeze storage was in the following order: ascorbic acid > tocopherol > BHA > control (P < 0.01). This data did not confirm the results of King et al (1995) and Serdaroglu and YildizTurp (2004), who found ascorbic acid inactive in preventing lipid oxidation on poultry at the end of the storage at -20°C for 6 weeks. When used in meat products at 0.025-0.05%, ascorbic acid and sodium ascorbate inhibited lipid oxidation and preserved the desirable meat flavour (Rhee et al 1997).…”
Section: Lipid Oxidationcontrasting
confidence: 56%
“…The results were not so convincing as those reported for α-tocopherol, and a lack of protective action of β-carotene has been reported (24). In the present work, broiler chickens were fed one of four diets supplemented with various amounts of α-tocopherol and β-carotene.…”
contrasting
confidence: 43%
“…Similarly, Warner and Frankel (16) referred to the effect of natural tocopherols in soybean oil in protecting added β-carotene. In poultry meat that contained 2.4 µg/g β-carotene was a prooxidant, and α-tocopherol counteracted the effects of β-carotene (25).…”
Section: Resultsmentioning
confidence: 99%